IDENTIFIKASI MOLEKULER TANAMAN PISANG RAJALAWE BERDASARKAN GEN INTERNAL TRANCRIBED SPACER (ITS) - Firly Putri Fardilla; Hermin Pancasakti Kusumaningrum; w wijanarka (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2017)
Banana is one type of horticultural commodities in a group of fruits that have a socio-economic value is high enough for the people of Indonesia. Bananas have different varieties, one banana type Rajalawe found in Central Java. Rajalawe molecular identification has not been done before. This study aims to determine the result of the identification of the molecular basis of Rajalawe based on genes Internal transcribed spacer (ITS), in search of identity and kinship Rajalawe. The study was conducted by isolating DNA using a method Rajalawe Doyle & Doyle, followed by ITS gene amplification and sequencing analysis. The results of gene amplification ITS produce PCR product of 643 bp. The base sequence of the sequencing results are used for the construction of phylogenetic trees. Sequence similarity analysis Rajalawe show 95% homology with Musa balbisiana and alkaline difference of 1%. Phylogenetic tree analysis showed Rajalawe have a close relationship with Musa balbisiana. However, bananas Rajalawe has several different characters with Musa balbisiana with different base sequences by 5% whereas the base sequence homology between the banana Musa balbisiana and Rajalawe with 95%.Keywords: Molecular Identification, Pisang Rajalawe, Universal Primer ITS, Musa balbisiana.